Pertanggungjawaban Pelaku Usaha Terhadap Konsumen Terkait Produk Makanan - Ane Fany Novitasari; Rokiyah Rokiyah; Shohib Muslim (Fakultas Hukum Universitas Islam Malang, 2022)
The obligation of a producer is not only to produce consumer needs, but to create and maintain a healthy business atmosphere is also part of the producer's duty. In fact, many food products cause people to get sick. This is because the perpetrators are negligent in producing food, but there are also business actors who deliberately make mistakes so that they can get a lot of profit. The purpose of this study is to analyze the accountability of business actors to consumers related to food products. This study uses a normative juridical method. The results of the study indicate that Article 2 of Law Number 8 of 1999 includes five principles which include the principle of benefit, the principle of justice, the principle of balance, the principle of security and consumer safety, and the principle of legal certainty. The responsibility of business actors to consumers regarding food safety is by making demands against food business actors who produce and sell dangerous food, namely by proving the guilt of the business actor with the principle of responsibility.